Sensory and Nutritional Quality of Madiga Produced from Composite Flour of Wheat and Sweet Potato - Idolo, Ifie (Pakistan Journal of Nutrition, 2011)
Madiga is a local bread product produced from wheat flour consumed by the people of the Niger Delta regions of Southern Nigeria. The use of sweet potato flour substitution in wheat flour at 0%, 15%, 20% and 25% each for the production of Madiga was investigated. Proximate analysis of the sample showed that there was a slight decrease in the protein and fat content with increasing sweet potato supplementation. On the other hand, the ash and crude fibre content increased with higher sweet potato supplementation. Carbohydrate contents ranged from 57.75-59.26%. Nutritional analysis of the Madiga samples showed an increase in the energy, Vitamin A, B6 C and magnesium contents as sweet potato flour substitution increased with the 25% supplementation having the highest values of 1023 kcal/100 g, 3.241 ug/100 g, 0.383 mg/100 g, 6.85 mg/100 g and 28 mg/100 g respectively. The results of sensory evaluation of the Madiga samples showed that no significant differences were observed between whole wheat Madiga and the sweet potato supplemented Madiga in sensory attributes of aroma, texture, taste and overall acceptability (p<0.05). In terms of Madiga colour, the 25% sweet potato supplemented Madiga sample had the highest scores. The findings from this work show that wheat substitution with sweet potato flour up to 25% can be adopted for improved nutritional quality and reduced cost in the production of Madiga.